Distance education in educational processes: Contributes significantly to learning (Docentes 2.0 Journal, 2020)
The fundamental purpose of this argumentative study is to point out the importance of educational transformation and its significant influence on learning, particularly related to the process of distance education, virtual teaching/learning environments (EVE/A) and technological skills present in the teacher and virtual student. Nowadays, it is essential to reform them from virtuality, through the intensive and efficient use of information and communication technologies (ICT), however, teachers with competence are required to change their pedagogical practice and effectively manage the content in the various virtual teaching / learning environments available at the “Fermín Toro” University. Currently, this institution is looking for innovative alternatives and strategies in order to provide answers and consolidate the teaching practice online according to the benefits requested to meet the requirements of creating a different conception to the traditional one, with emphasis on self-training of being, optimizing time and the virtual classroom. The research was documentary, through the technique of reading, literature review and interpretation of the authors' writings, this allowed to consolidate the author's position. Finally, the central question of the research emerges. Does the use of virtual classrooms significantly influence learning? Which was revealed through the analysis, articulation and integration of the keywords.
Keywords: Distance education; virtual teaching/learning environments; technological skills